The rise of the outcast emperors: State, conflict, and usurpation in Late Antiquity (285-395) - Sathler, Larissa Rodrigues (Romanitas - Revista de Estudos Grecolatinos, 2021)
Book review of: SILVA, Gilvan Ventura da. A escalada dos imperadores proscritos: Estado, conflito e usurpação na Antiguidade Tardia (285-395). Vitória: GM Editora, 2018. 166 p.